2015
DOI: 10.4103/1947-2714.161250
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the relationship between musculoskeletal discomforts and occupational stressors among nurses

Abstract: Background:Stress in nurses may increase the prevalence of musculoskeletal discomforts.Aim:The aim of this study was to determine the prevalence of musculoskeletal discomforts and job stress among nurses and to investigate the association between musculoskeletal discomforts and occupational stressors.Materials and Methods:In this cross-sectional study, 144 nurses in one of the main referral hospitals of Tehran-Iran were randomly selected and studied. Data were collected by HSE job stress questionnaire and The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 23 publications
(24 reference statements)
0
9
0
Order By: Relevance
“…Burnout symptoms, which were associated with physical loads, were pain in upper limbs, in the cervical region, lumbar region and may be related to irritability (7) . Situations of irritability and stress were observed among nursing workers and associated with musculoskeletal injuries, especially in the neck, shoulders, back and waist regions (19) .…”
Section: Discussionmentioning
confidence: 99%
“…Burnout symptoms, which were associated with physical loads, were pain in upper limbs, in the cervical region, lumbar region and may be related to irritability (7) . Situations of irritability and stress were observed among nursing workers and associated with musculoskeletal injuries, especially in the neck, shoulders, back and waist regions (19) .…”
Section: Discussionmentioning
confidence: 99%
“…Research in occupational medicine has identified a number of physical and psychosocial risk factors for the development of work-related MSDs [13][14][15][16][17][18][19][20][21][22][23]. Previous studies have shown that MSD are directly caused by physically demanding work and strenuous working conditions, such as lifting or carrying heavy loads, tiring positions, awkward posture, or repetitive movements [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, MSDs were also found to be related and associated with psychologically stressful work, i.e. with psychosocial work factors and work-related stressors such as time pressure, low job control, little social or supervisor support, effort-reward imbalance, or work-life conflict [16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Work-related stress among nurses affects both individual and organizational functioning as well as the healthcare provided. Literature suggests that it is associated with musculoskeletal disorders[ 4 5 ] and locomotor diseases,[ 6 ] high rates of anxiety[ 7 8 ] and depression,[ 9 10 ] high burnout levels,[ 11 ] reduced job satisfaction,[ 12 ] absenteeism,[ 13 ] and high turnover intention,[ 14 ] whereas it is negatively associated with nurses' patient care behaviors. [ 15 ]…”
Section: Introductionmentioning
confidence: 99%